TESTING THE ORIGIN OF HIGH-ENERGY COSMIC RAYS - Vladimirov, A E; Johannesson, G; Moskalenko, I V; Porter, T A (The Astrophysical journal, 2012)
Recent accurate measurements of cosmic-ray (CR) protons and nuclei by ATIC-2, CREAM, and PAMELA reveal (1) unexpected spectral hardening in the spectra of CR species above a few hundred GeV per nucleon, (2) a harder spectrum of He compared to protons, and (3) softening of the CR spectra just below the break energy. These newly discovered features may offer a clue to the origin of the observed high-energy Galactic CRs. We discuss possible interpretations of these spectral features and make predictions for the secondary CR fluxes and secondary-to-primary ratios, anisotropy of CRs, and diffuse Galactic gamma -ray emission in different phenomenological scenarios. Our predictions can be tested by currently running or near-future high-energy astrophysics experiments.